2020
DOI: 10.1186/s12891-020-03232-2
|View full text |Cite
|
Sign up to set email alerts
|

Tibial and femoral osteotomies in varus deformities - radiological and clinical outcome

Abstract: Background: Varus deformities of the knee are frequently corrected by osteotomies, which should be performed at the level of origin. But in contrast to high tibial osteotomies (HTO), little data exists for distal femoral osteotomies (DFO). This study evaluates radiological and clinical outcomes after valgisation osteotomies in the proximal tibia and distal femur. Methods: We used an observational cohort study design and prospectively performed preoperative long standing radiographs (LSR), lateral x-rays and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…Four of these patients shifted to moderate and 1 to very heavy work intensity. The general duration of the inability to work was 12.2 ± 4.4 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) weeks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four of these patients shifted to moderate and 1 to very heavy work intensity. The general duration of the inability to work was 12.2 ± 4.4 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) weeks.…”
Section: Resultsmentioning
confidence: 99%
“…All patients who were unable to work before surgery due to symptomatic varus knee osteoarthritis were able to return to work with moderate or even very heavy workloads. The duration of the inability to work was 12.2 ± 4.4 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) weeks with an improved pain situation. Based on these results, surgeons can preoperatively assume that patients will return to work following DLO in the short term regardless of the work intensity.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only one study has reported results after both, DFO and HTO to correct varus malalignment. Fürmetz et al [ 16 ] prospectively evaluated 25 consecutive patients undergoing realignment osteotomy of a varus deformity. HTO was performed in 17 patients and DFO in 11 patients.…”
Section: Discussionmentioning
confidence: 99%
“…HTO was performed in 17 patients and DFO in 11 patients. After a mean follow-up of 47 months, improvement in all clinical scores was observed, without differences between the two techniques [ 16 ]. However, the small patient cohort and relatively short follow-up period limit the conclusion of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Akaoka et al [ 35 ] did not report any significant difference between the two cohorts with regard to patellofemoral biomechanics. However, Fürmetz et al [ 36 ] reported a significant reduction in the patellar height for the HTO group compared with the DLO cohort.…”
Section: Systematic Reviewmentioning
confidence: 99%